Penyelesaian Pembiayaan Bermasalah (NPF) Akad Murabahah - Dewi, Yuni Ratna; Nashirudin, Muh (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The problem that often arises from the distribution of financing is the case of delinquent repayment of financing that can disrupt the liquidity and profitability of financial institutions. Murabaha financing is a product that is in great demand by the lower middle class because the process is very simple and faster by using a sale and purchase agreement with collateral or collateral. The purpose of this study was to analyze the resolution of non-performing finance (NPF) at KSU JMS Karanganyar. This research uses a qualitative descriptive approach. Data collection methods with interviews, observation and documentation. Factors that influence the emergence of non-performing financing are triggered by internal factors and external factors. Internal factors include weaknesses in financing analysis, financing period, less than optimal control from LKS, and less than optimal risk screening. External factors include customer bad faith, declining customer approach, disasters such as the covid 19 pandemic outbreak and customer carelessness in the use of funds. The policies taken by KSU JMS Karanganyar to reduce NPF include On The Spot, collection, restructuring, settlement through collateral, write off, and the formation of a risk team. The success of this NPF reduction apart from the policies taken is also influenced by the improvement of the national economy and the economy of the community.